Nitrogen effects on radiation response in 12Cr ferritic/martensitic alloys. (December 2020) - Aydogan, E.; Gigax, J.G.; Parker, S.S.; Eftink, B.P.; Chancey, M.; Poplawsky, J.; Maloy, S.A.
Abstract: Ferritic/martensitic steels are one of the best candidates for structural materials for high dose applications in next generation nuclear reactors. The composition of structural materials must be optimized for reliable service during irradiation. This study reports the effect of interstitial nitrogen on radiation response in 12Cr ferritic/martensitic HT9 steels having a controlled nitrogen concentration. Results show that a high amount of 'free' nitrogen in the matrix stabilizes the interstitial clusters which leads to (i) larger loop sizes (ii) lower loop density and (iii) slightly reduced radiation induced hardening. It also affects diffusion mechanism of Ni and formation of Ni/Si-rich precipitates. Graphical abstract: Image, graphical abstract